Catechins Green Tea Clones GMB4 Inhibit Inflammation Process of Atherosclerosis Through Decreasing TNF-Α Levels - Susanti, Erna; Suratno, Febiyanti (Journal of Islamic Pharmacy, 2016)
Catechins Green tea clones GMB4 are potential natural subtances to inhibit inflammation process in atherosclerosis. The purpose of this research to determine activity of Catechins Green tea clones GMB4 to decrease TNF-α levels, as well as to determine optimal dose of Catechins. This research was conducted at the Laboratory of Physiology of the University of Brawijaya. The method used in this research is completely randomized design with five treatments: (1) Mice with standard feed (2) mice with high-fat diet (3) mice with high-fat diet + catechins 3mg / day (4) mice with a diet high fat + catechin 6mg / day (5) mice with high-fat diet + catechin 24mg / day. The treatment was done for 60 days and measured levels of TNF-α at the end of the research. The results showed that Catechins green tea clones GMB4 can inhibit the inflammatory process in atherosclerosis through decreasing levels of TNF-α at doses of 3mg / day. The conclusion of this research is catechins at a dose of 3 mg / day can inhibit inflammation in atherosclerosis significantly. Keywords : GMB 4 green tea clones, Catechins, inflammation, TNF-α